Putting the "Me" in endorsement: Understanding and conceptualizing dimensions of self-endorsement using intelligent personal assistants. (June 2021) - Hamilton, Kristy A; Lee, Seo Yoon; Chung, Un Chae; Liu, Weizi; Duff, Brittany RL
Self-endorsement—depicting the "self" as an endorser of a brand—represents a potentially powerful advertising strategy made possible by new media. This experiment tests the hypothesis that receiving brand recommendations from an intelligent personal assistant believed to be tailored to one's own characteristics and consumer interests yields higher brand attitude and purchase intention toward the (self-endorsed) brand than receiving brand recommendations from a typical, but not self-tailored, intelligent personal assistant. Because endorsement is a well-known and highly effective advertising strategy, this is a high bar. We present evidence for self-referencing as an underlying mechanism, and perceived interactivity and identification as boundary conditions of self-endorsing. Consumers may show skepticism toward advertising but may not know how to be skeptical of themselves. As consumers outsource their tasks and decisions to new artificial intelligence (AI)-driven devices, they will need to be attentive to new media biases that threaten productive use of these devices.